Physico Chemical Properties and Moisture Characteristics of Soils as Influenced by forest Fire - Banerjee, S. P.; Chand, Sumer (Indian Forester, 1981)
In order to quantify and document the influence of forest fire on physico-chemical and moisture characteristics of soil, a study was and undertaken in Sukna I, Kurseong Forest Division, West Bengal. Fire affected the soil by drastic reduction of organic carbon, total nitrogen, cation exchange capacity, exchangeable calcium and magnesium, available P2O5 and K2O. Soil reaction became less acidic. Moisture characteristics of the affected soils were radically changed with substantial reduction in 1/3-bar moisture as well moisture retention at different tensions, and inability to retain any moisture beyond 8.l-bar tension. Water holding and available water capacities were considerably reduced.